ASSESSMENT OF THE FISHING TECHNIQUES IN BALI SARDINELLA FISHERY IN PENGAMBENGAN FISHING PORT, BALI, INDONESIA: KAJIAN TEKNIK PENANGKAPAN IKAN PADA PERIKANAN LEMURU DI PELABUHAN PERIKANAN NUSANTARA PENGAMBENGAN, BALI, INDONESIA - Jaya, Made Mahendra; Khikmawati, Liya Tri; Larasati, Rakhma Fitria; Sudananjaya, Bagus (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Fisheries management with an ecosystem approach is essential to implement. This approach aims to achieve sustainability and balance in socio-economic, ecological, and more effective fisheries governance dimensions. The aspect assessed in this study was fishing techniques. The assessment was divided into six indicators: fishing methods, fishing capacity, selectivity of fishing gear, modification of fishing gear, suitability of fishing boat size and function, and certified fishing boat crew. This study aims to assess the status of Bali sardinella fishery resources in Bali Strait Waters, especially related to fishing techniques. We conducted research activities at Nusantara Fishing Port (PPN) Pengambengan from March to July 2023. Data collection used several methods, including interviews, surveys, and fish size sampling. The study results showed that the indicator of illegal or destructive fishing techniques or methods obtained a score of 3, and modification of the fishing gear used also received a score of 3. Fishing capacity, selectivity of fishing gear, and suitability of function and size of fishing boat used, based on legal documents, received a score of 3, 3, and 1, respectively. In contrast, certified fishing crews received a score of 1. Overall, the composite assessment in the fishing technique domain reached 90%, indicating that the Ecosystem Approach to Fisheries Management (EAFM) principles have been implemented well.